Investigating the interaction between some of Bipolaris sorokiniana’s toxins and the Gα Subunit of the Wheat G-Protein using bioinformatics tools - Leen Dayoub; Yanal Alkuddsi; Nasser Thallaj (University of Thi-Qar Journal of agricultural research, 2023)
Spot blotch disease of wheat, caused by the fungus Bipolaris sorokiniana (Sacc.) Shoem., produces several toxins like: prehelminthosporol, helminthosporol, helminthosporic acid, sorokinianin, Bipolaroxin. These toxins interact with the plant and thereby increase the symptoms of small dark lesions and huge yield losses in different regions around the world so there is an urgent need to decipher the molecular interaction between wheat and those toxins for in-depth understanding of host–pathogen interactions. In the present study, we have modeledthe three-dimensional structure of G-protein alpha subunit from Triticum aestivum as G-protein was shown that it is an important player behind the resistance to many plant diseases. Molecular docking studies were performed using the active site of the modeled G-protein alpha subunit from T. aestivumand some of fungus’s toxins followed by molecular dynamics (MD) simulation studies to explore the stability, conformational flexibility, and dynamic behavior. Protein-ligand interaction study revealed one H-bond formed by Lys302 and hydrophobic contacts formed by Tyr159, Gly162, Val167, Asp256, Gln257 and Ile298 with prehelminthosporol, Protein-ligand interaction study revealed H-bond formed three H-bonds formed by Tyr159, Gly162, and Asp256 and hydrophobic interactions formed by Ser160, Cys161, Ser162, Ile298, Lys302 and Val306 with helminthosporic acid. Protein-ligand interaction study revealed two H-bond formed by His172, Arg301 and hydrophobic interactions by Tyr159, Pro168, Asp169, Ile298 and Lys302 with sorokinianin. Protein-ligand interaction study revealed H-bond formed six H-bonds mainly formed by Glu29, Ser30, Lys32, and Ala177. In addition to H-bonds, hydrophobic contacts formed by Gly28, Gly31, Ser33, Thr34, Arg78, Val179, Thr181 and Gly209 with Bipolaroxin were also observed.